APPLICATION OF LEADERSHIP STYLES IN DIGITAL HEALTHCARE SYSTEMS - Jayanagara, Oscar (Universitas Pelita Harapan, 2024)
Leadership will always change according to the times, including leading in digital era. Leadership is the art of inviting and moving other people to work to achieve goals. This research aims to analyze the relationship between transformational leadership and LMX theory that provide valuable frameworks for leadership in the digitalization era by promoting adaptability, innovation, employee engagement, collaboration, and the development of strong interpersonal relationships in a technologically driven work environment. The qualitative approach is used utilizing the databases Semantic Scholar, Google Scholar and PubMed. There is a strong relationship between traits (intelligence, personality, integrity) and leadership. Digital era is an era where society is centered on systems that are integrated online in solving social problems and balancing economic growth. In this digital era, healthcare leaders need to improve their tech savvy skill so they can guide their organizations in adopting and leveraging these technologies. They need to be more proactive, be innovative and dynamic, and set a good example in order to bring the organization up ahead. To improve the quality of digital health services, effective leadership is required.